2018
DOI: 10.3322/caac.21548
|View full text |Cite
|
Sign up to set email alerts
|

Equitably improving outcomes for cancer survivors and supporting caregivers: A blueprint for care delivery, research, education, and policy

Abstract: Cancer care delivery is being shaped by growing numbers of cancer survivors coupled with provider shortages, rising costs of primary treatment and follow‐up care, significant survivorship health disparities, increased reliance on informal caregivers, and the transition to value‐based care. These factors create a compelling need to provide coordinated, comprehensive, personalized care for cancer survivors in ways that meet survivors’ and caregivers’ unique needs while minimizing the impact of provider shortages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 132 publications
(214 reference statements)
3
145
0
1
Order By: Relevance
“…Virtually all patients with cancer have multiple appointments with multiple providers for workup and treatment. After completion of treatment, patients should receive coordinated survivorship care in multiple settings, including specialty and primary care …”
Section: Delivery Of Cancer Control Services In the United Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Virtually all patients with cancer have multiple appointments with multiple providers for workup and treatment. After completion of treatment, patients should receive coordinated survivorship care in multiple settings, including specialty and primary care …”
Section: Delivery Of Cancer Control Services In the United Statesmentioning
confidence: 99%
“…This article is part of the Cancer Control Blueprint series, which identifies opportunities for improving cancer control to reduce disparities in the burden of cancer morbidity and mortality in the United States. Prior articles have described the extent of disparities, and highlighted opportunities to improve cancer prevention, screening, and cancer survivorship care . Herein, we synthesize published research to describe cancer care delivery in the United States, including cancer prevention, early detection and diagnosis, treatment, survivorship, and end‐of‐life care; provide an overview of the US health care system; and identify goals for a high‐performing health care system to reduce disparities in the burden of cancer in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research should test stepped care approaches to cancer rehabilitation in which providers tailor the intensity of care and the site and method of care delivery based on patient need and many patients can receive services at home through telemedicine. [34][35][36][37] Examining the perspectives of patients, clinicians, and health care administrators regarding the use of different levels and modalities of care (eg, telemedicine approaches 37 ) and community-based resources for interventions such as exercise prescriptions would allow for the evaluation of preference and perceived value. As Berwick notes, 29 research also is needed to understand how best to engage patients in their care in ways that optimize outcomes in lieu of the increasing practice of shifting more costs to patients to facilitate engagement.…”
Section: Introductionmentioning
confidence: 99%
“…However, most nurses agreed on the importance of MetS‐related management in cancer survivors and suggested several educational strategies. Alfano et al () suggested that efforts are needed in three priority areas: first, “implementing routine assessment of cancer survivors’ need and functioning”; second, “facilitating personalised, tailored care information and referrals from diagnosis forward for survivors, shifting care from point of care to point of need wherever possible”; and third, “disseminating and supporting the implementation of new care methods and interventions”. Applying these suggestions to the results of the present study can advocate the necessity of continuous assessment of the MetS‐related needs of cancer survivors and the related knowledge level of oncology nurses to provide appropriate individualised care and develop new education methods for effective MetS management among cancer survivors.…”
Section: Discussionmentioning
confidence: 99%